The importance of upper body strength testing and training for performance of high-intensity actions in professional soccer players: A survey exploring perceptions and current practices of soccer strength and conditioning coaches - Curovic, I.; Grecic, D.; Rhodes, D.; Alexander, J.; Harper, D. J. (International Journal of Strength and Conditioning, 2025)
This study aimed to investigate the perception of soccer strength and conditioning (S&C) coaches on the importance of upper body (UB) strength training for the performance of high-intensity actions (HIA) (i.e., sprinting, repeated sprint ability, change of direction, and jumping) in professional soccer players, and to identify current practices with regards to UB strength testing and training methodologies within this sport. Eighty-six S&C coaches working with professional soccer players volunteered to complete the survey. Twenty-two fixed responses and three open-ended questions were grouped into three sections: (a) demographic information, (b) perspectives on the importance of UB strength and UB strength training for HIA, and (c) current practices of UB strength training in soccer. Frequency analysis was used to assess fixed response questions, and thematic analysis established clear and recognisable themes for open-ended questions. Relative to "not important" options, UB strength was perceived as important for all HIA, especially for jumping (89%) and acceleration (87%). Coaches strongly supported the idea that UB strength plays a role in enhancing HIA, with particular influence on jumping (100%), acceleration (97%) and COD (93%). This positive influence is believed to be realised via improved force transmissions (97%) and neural drive (94%). Notably, however, surveyed coaches overwhelmingly use moderate resistance in their sessions (100%) without substantial emphasis on high-velocity contractions (64%). In conclusion, S&C practitioners value UB strength training for enhancing the performance of HIA in professional soccer players. Further research is needed to explore this link and provide clearer guidance on the implementation of UB strength training in professional soccer.